The hydraulics of open channel flow an introduction ; basic principles, sediment motion, hydraulic modelling, design of hydraulic structures - Chanson, Hubert
New edition of the book praised by professionals, academics, students and researchers alike as the most practical modern textbook on open channel flow available.